Guiding catheter extension compatibility for high speed rotational atherectomy - Pawłowski, Tomasz; Modzelewski, Paweł; Stachura, Michał; Śliwiński, Zbigniew; Gil, Robert J. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Coronary calcification is one of the features that characterize atherosclerosis. The location of a calcific plaque may vary from case to case [1]. Some distal locations may affect procedural outcomes of coronary angioplasty, resulting in impaired device deliverability. In these cases, guiding extension catheters have been widely introduced into practice to overcome the problem of poor deliverability and guiding catheter support. In some patients, calcified lesions are located distally and rotational burr deliverability is also impaired.